Utilization of Museum Galunggung as a Source for Local History Learning at SMA IT Riyadlussholihin Tasikmalaya - Ramdani, Rizki Ahmad; Brata, Yat Rospia; Sudarto, Sudarto (Universitas Galuh, 2025)
This study is driven by the critical role of history education in shaping the identity and character of younger generations within the contemporary context, emphasizing the integration of local history to reflect national diversity. Modern pedagogical frameworks incorporate various instructional strategies, notably observational learning through experiential visits to historical sites such as museums. Museums serve as effective educational tourism venues and function as pertinent media to support history curriculum delivery. This research investigates the strategic planning and educational impact of employing Galunggung Museum as a history learning resource for Grade X students at SMA IT Riyadlussholihin Tasikmalaya. The primary objective is to enhance students' motivation and awareness of local historical heritage. Employing a qualitative methodology with a descriptive-analytical approach, the study finds that integrating the Galunggung Museum into the learning process effectively addresses students’ lack of engagement and comprehension in history subjects. Consequently, the study advocates for history educators to adopt, adapt, and innovate pedagogic methods tailored to student characteristics to deepen local history understanding. This research offers practical recommendations for optimizing museum-based learning as an innovative pedagogical tool to improve educational outcomes in local history.